Electrical conduction in calcium lanthanum titanium cobalt oxide, Ca1-xLaxTi1-xCoxO3 (x ≤0.50) - Parkash O.; Kumar D.; Prasad C.D.; Tewari H.S. (My University, 2025)
The DC resistivity and the Seebeck coefficient have been measured as a function of temperature in the system Ca1-xLaxTi1-xCoxO3 for the samples with x≤0.50 in the range 300-800 K. AC conductivity has been measured as a function of temperature and frequency for the samples with x ≤0.20 AC conductivity data indicate that conduction occurs due to hopping of charge carriers among localised sites giving rise to a Debye-type loss process at low temperatures. Results of AC resistivity combined with DC resistivity show that at high temperatures electrical transport occurs by excitation of charge carriers at the valance band edge and hopping at energies close to it. © 1990 IOP Publishing Ltd.